HIF1α epigenetically repressed macrophages via CRISPR/Cas9-EZH2 system for enhanced cancer immunotherapy - Dong, Yan (Bioact Mater, 2021)
Immune suppressive microenvironment in tumor emerges as the main obstacle for cancer immunotherapy. In this study, we identified that HIF1α was activated in the tumor associated macrophages and acted as an important factor for the immune suppressive microenvironment. Epigenetically silencing of Hif1α via histone H3 methylation in the promoter region was achieved by CRISPR/dCas9-EZH2 system, in which histone H3 methylase EZH2 was recruited to the promoter region specifically. The Hif1α silenced macrophage, namely HERM (Hif1α Epigenetically Repressed Macrophage) manifested as inheritable tumor suppressing phenotype. In the subcutaneous B16-F10 melanoma syngeneic model, intratumoral injection of HERMs reprogrammed the immune suppressive microenvironment to the active one, reducing tumor burden and prolonging overall survival. Additionally, HERMs therapy remarkably inhibited tumor angiogenesis. Together, our study has not only identified a promising cellular and molecular target for reverting immune suppressive microenvironment, but also provided a potent strategy for reprogramming tumor microenvironment via epigenetically reprogrammed macrophages.